Prehistoric man human evolution - Goldhil Entertainment (Firm).; Full Circle Entertainment (Camarillo, Calif. Goldhil Entertainment, 2007)
"Viewers come face to face with fascinating ancient creatures who looked something like apes but walked upright. We learn how they lived in their foraging societies; what their life may have been like; how they fashioned tools out of stone, wood and bone; and how scientists determine the age of the fossils that give us windows to their world. Moreover, we examine patterns that developed, which give us insight into human adaptation and evolution."--Container.
Pt. 1. Human evolution -- pt. 2. Human evolution in the Lower Paleolithic Age -- pt. 3. Human evolution in the Middle and Upper Paleolithic Age.
Originally released in 2002.
Keywords: Human evolution -- Juvenile films; Prehistoric peoples -- Juvenile films; Anthropology -- Juvenile films